2008
DOI: 10.2174/157340608786242115
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 4-amino-5-cyano-2, 6-Disubstituted Pyrimidines as a Potential Antifilarial DNA Topoisomerase II Inhibitors

Abstract: A novel series of 4-amino-5-cyano-2, 6-disubstituted pyrimidines have been synthesized and evaluated for their in vitro antifilarial DNA topoisomerase II activity against filarial parasite Setaria Cervi. In particular compounds bearing 4-chloro-phenyl substitutent at position-6, exhibited strong inhibition at 40 microg/mL and 5 microg/mL concentration. The present study based on the biological results obtained, suggests that the nature of substitutent at position-4 in the phenyl ring directly affects DNA topoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…In similar study Ciprofloxacin was shown antifilarial activity against Brugia malayi parasite [23]. Novobiocin antibiotics also found to be active in many experiment against Brugia malayi [24,25]. These results revealed that some active molecules present in this plant extract might be responsible for the real antifilarial effect.…”
Section: Disscusionmentioning
confidence: 56%
“…In similar study Ciprofloxacin was shown antifilarial activity against Brugia malayi parasite [23]. Novobiocin antibiotics also found to be active in many experiment against Brugia malayi [24,25]. These results revealed that some active molecules present in this plant extract might be responsible for the real antifilarial effect.…”
Section: Disscusionmentioning
confidence: 56%
“…Using organic solvents in the reaction did not increase yields (entries 9-12), due to poor solubility of the S-alkylisothiouronium salts. Fortunately, it was found that when the amount of aldehyde was increased slightly from 1 to 1.1 equivalent better yields were achieved (entries [14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…2-Alkylthio-4-amino-5-cyano-6-aryl(alkyl) pyrimidines represent one kind of the important PFSPs, and their pyrimidine and pyrimidine-fused heterocyclic derivatives were found to have special pharmacological activities. For example, derivatives of A exhibit topoisomerase II inhibitory activity against filarial parasite Setaria Cervi [16], compounds B show DPP-IV inhibitory activity against type 2 diabetes [17,18], and compounds C display adenosine A2a receptor agonistic activity for treating glaucoma [19]. The pyrimidine-fused heterocyclic compounds D and E are PDK1 inhibitors and TLR modulators, respectively ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of DNA topoisomerases in various filarial parasites and their different life stages viz. B. malayi, Setaria cervi and Acanthocheilonema viteae has been demonstrated and used as target for development of new antihelminthic compounds (Chandra et al, 2004;Kumar et al, 2008;Pandya et al, 1999). Recently hexokinase has been shown as potential chemotherapeutic target (Singh et al, 2008).…”
Section: Introductionmentioning
confidence: 99%